Summation by riesz means of the fourier-laplace series - Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik; Akhmedov, Anvarjon (University of Nis, 2018)
In this work, weinvestigate conditions for summability of the Fourier-Laplace series of integrable functions by Riesz means. The kernel of Riesz means is estimated through comparison with the Cesaro means. Properties of D and D* points are required in obtaining this estimation. © 2018, University of Nis. All rights reserved.